Studi Persepsi Meningkatkan Kinerja Pegawai dengan Employee Engagement dan Iklim Organisasi - Lustanti, Tania; Senen, Syamsul Hadi; Masharyono, Masharyono (Business Education Program of Universitas Pendidikan Indonesia, 2019)
Abstract: The success of achieving organizational goals is largely determined by the roles and responsibilities of employees in it. Employees are required to be able to support and be involved in every activity to achieve goals in the organization. The inability of employees to do work optimally will cause problems in employee performance. Employee performance can affect an organizational performance which has an impact on the realization of the organizational goal. This article provides a numerical study of 1) the effect of employee engagement on performance, and 2) the effect of organizational climate on performance. This research employed verificative study through an explanatory survey using sampling amounting to 84 employees in public organization as respondents through questionnaires. The data were analyzed by using multiple linear regression technique through Statistical Product for Service Solutions (SPSS) 24.0 for windows. The results of the research indicate that the 1) employee engagement has an effect on performance by 49% or in the moderate category, 2) organizational climate has an effect on performance by 76,6% or in the strong category. This result indicated that higher employee engagement will be higher performance, as well as the organizational climate, the better the climate in the organization will be the higher employee performance and vice versa.Â